Implikasi Hukum Konsep Blue Economy Terhadap Pemanfaatan Sumber Daya Laut di Zona Ekonomi Eksklusif Indonesia: Analisis Keseimbangan antara Konservasi dan EksploitasiLetter - Badaruddin Badaruddin (Journal of Innovative and Creativity, 2025)
The study aimed to examine how legal norms can harmonize economic utilization and environmental conservation within Indonesia’s maritime governance framework while identifying the gaps between international legal frameworks—particularly the United Nations Convention on the Law of the Sea (UNCLOS) 1982—and Indonesia’s national regulations governing marine resource management. This research highlights the urgency of aligning international and national legal instruments to ensure sustainable ocean resource utilization while safeguarding national sovereignty and promoting the welfare of coastal communities. Using a normative juridical approach supported by statute and conceptual analyses, the study relied on primary legal materials such as UNCLOS 1982, Law No. 32 of 2014 on Marine Affairs, and Law No. 45 of 2009 on Fisheries, complemented by secondary sources including academic journals, policy papers, and international reports. Data were analyzed qualitatively through systematic, teleological, and comparative interpretations to assess the coherence between international and national maritime legal frameworks. The findings indicate that although Indonesia has adopted Blue Economy principles in its maritime policy, implementation remains limited due to overlapping regulations, weak institutional coordination, and inadequate law enforcement, which collectively hinder sustainable and integrated marine resource management within Indonesia’s Exclusive Economic Zone (EEZ). The study concludes that strengthening legal harmonization, enhancing institutional capacity, and promoting participatory governance are essential to establish an effective Blue Economy framework, emphasizing the need for a unified maritime legal system that integrates economic, ecological, and social justice principles to achieve sustainable and equitable management of Indonesia’s marine resources.